Case Report: Heterozygous Germline Variant in EIF6 Additional to Biallelic SBDS Pathogenic Variants in a Patient With Ribosomopathy Shwachman–Diamond Syndrome - Taha, Ibrahim; Foroni, Selena; Valli, Roberto; Frattini, Annalisa; Roccia, Pamela; Porta, Giovanni; Zecca, Marco; Bergami, Elena; Cipolli, Marco; Pasquali, Francesco; Danesino, Cesare; Scotti, Claudia; et al. (Frontiers in Genetics, 2022)
Background: Shwachman-Diamond Syndrome (SDS) is a rare autosomal recessive ribosomopathy mainly characterized by exocrine pancreatic insufficiency, skeletal alterations, neutropenia, and a relevant risk of haematological transformation. At least 90% of SDS patients have pathogenic variants in SBDS, first gene associated to the disease with very low allelic heterogeneity: three variants, derived from events of genetic conversion between SBDS and its pseudogene, SBDSP1, provide the alleles observed in about 62% of SDS patients. Methods: We performed a reanalysis of available WES files of a group of SDS patients with biallelic SBDS pathogenic variants, studying the results by next bioinformatic and protein structural analysis. Parallelly, a careful clinical attention was done in the patient focus of this study. Results: We found in one SDS patient in EIF6 gene a germline heterozygous missense variant (c.100T>C; p. Phe34Leu), that has been confirmed in the patient and inherited from his mother. This variant has a very low frequency, and it impairs EIF6 protein activity, stability and folding. Conclusion: This study focused on the hypothesis that EIF6 germline variant mimics the effect of somatic deletions of chromosome 20, always including the locus of this gene and similarly may rescue the ribosomal stress and ribosomal dysfunction due to SBDS mutations. It is likely that this rescue may contribute to the stable and not severe haematological status of the proband and may reaffirm its potential towards a therapeutic approach.